Green extraction and valorization of by-products from food processing - Barba, Francisco (Francisco J.) (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
Generating of agricultural wastes and by-products during the production, processing and consumption of agricultural commodities is unavoidable and over the last decades, an increased public interest has been shown in the challenge of food wastage. Apart from its significant quantities, the physicochemical characteristics of the various agricultural waste and by-products denote that there is immense potential for their reuse, recycle, and valorisation through various different processes. Green Extraction and Valorization of By-Products from Food Processing provides an overview about the valorization or reuse of agricultural wastes and by-products during the production, processing and consumption of agricultural commodities. Waste disposal and by-product management in food processing industry pose problems in the areas of environmental protection and sustainability. However, they could be a great source of valuable nutraceuticals, which can be used to deal with the prospects of feeding fast growing population in 21st century. Features: Gives detailed guidance and presents case-studies about valorization of food wastes and by-products Shows the main conventional and innovative extraction techniques for food waste and by-products valorization Provides an estimated idea regarding the recovery of high-added value compounds Discusses the recovery of high-added value compounds Perspectives originated from the enormous amounts of food related materials that are discharged worldwide and the existing technologies, which promise the recovery, recycling and sustainability of high-added value ingredients inside food chain will be discussed in this book. This book is of value to academics, research institutes, and food industry engineers particularly the research and development professionals who are looking for effective management and utilization of food processing wastes and byproducts. In addition, it is suitable for undergraduate, post- graduate students, research scholars, postdoctoral fellows and faculty members from universities and colleges who pursue academic careers in Food Technology, Food Biotechnology, Fermentation and Bioengineering, Bioprocess Technology, Food science and Technology.
4 Enzymes5 Glycosaminoglycans; 6 Chitin and Chitosan and Chitooligosaccharides; 7 Collagen, Gelatins, and Derivatives; 8 Mineral Fraction and Bioapatites; 9 Silage, Biosilage, and Marine Peptones; 10 Conclusion; References; Chapter 5: Recovery of Antioxidant Bioactive Compounds from Sweet Potato and By-Products; 1 Introduction; 2 Sweet Potato and By-Products as Source of Antioxidant Bioactive Compounds and Antimicrobials; 2.1 Polyphenols; 2.2 Carotenoids; 2.3 Antimicrobial Activity of Sweet Potato Leaf Extracts; 3 Conclusion; Acknowledgments; References
OCLC-licensed vendor bibliographic record.
Keywords: Food industry and trade -- Waste minimization; Source reduction (Waste management); TECHNOLOGY / Food Science